(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Effective corporate governance is now a need for every business that wants to succeed since it can raise a company's valuation and increase its potential profitability. Panel data regression was used for the objective of studying the relationship between Corporate Governance Practices and Corporate Performance. 10 companies selected from FMCG sectors on the basis of market Capitalizations have been analyzed. It was found that audit meetings have positive relation with ROA and ROCE while negative relation with P/E, number of independent directors has positive association with EPS while negative association with ROA and number of meetings has negative association with EPS.